Status Mental dan Kemampuan Interaksi Sosial Lanjut Usia - Joko Susanto; Makhfudli Makhfudli; Khotibul Umam (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The human life cycle is a process of growth and development physically and mentally. Physical and mental changes in the elderly occur due to degenerative processes, so that there will be limitations in activities, memory and speaking abilities. The existence of these limitations, affects social interactions with other people which tend to be reduced and passive. Decreased social interaction in the elderly can cause a sense of isolation, feeling useless, so that the elderly tend to be alone. This Study aimed to identify the association between mental status and soscial interaction capacity among the elderly. This research used correlational with a cross sectional design. Data were obtained from SPMSQand social interaction capacity elderly questionnaire. The study used a sample of 91 respondents, with a simple random sampling technique. Data analysis used Spearman rho test. The results showed that the majority (57,1%) of the elderly had minor intellectual impairment, and most (5,.9%) of the elderly had moderate social interaction skills. The results of the Spearman test p=0,001 and r=0,353, meaning that there is a relationship between mental status and the social interaction ability of the elderly, the strength of the correlation is moderate and the correlation is positive. The conclusion of this study is that there is a significant relationship between mental status and the social interaction skills of the elderly.Keywords: mental status; social interaction; elderlyABSTRAKSiklus kehidupan manusia selalu tumbuh dan berkembang baik secara fisik maupun mental. Perkembangan fisik dan mental pada lansia mengalami proses degeneratif, sehingga terjadi penurunan aktifitas, mengingat dan kemampuan berbicara. Adanya penurunan tersebut, berpengaruh pada interaksi sosial dengan orang lain sehingga berkurang dan pasif. Menurunnya interaksi sosial lansia dapat menyebabakan perasaan terisolasi, merasa tidak berguna sehingga menyebabkan lansia cenderung menyendiri. Tujuan penelitian adalah mengidentifikasi adanya hubungan status mental dengan kemampuan interaksi sosial lansia. Penelitian menggunakan studi korelasional dengan pendekatan cross sectional. Instrumen penelitian kuesioner SPMSQ dan kuesioner Kemampuan Interaksi Sosial Lansia. Penelitian menggunakan sampel 91 responden, dengan teknik simple random sampling. Analisis data menggunakan uji Spearman. Hasil penelitian menunjukkan mayoritas (57,1%) lansia mengalami kerusakan intelektual ringan, dan sebagian besar (54,9%) lansia memiliki kemampuan interaksi sosial sedang. Hasil uji Spearman p=0,001 dan r=0,353, berarti terdapat hubungan status mental dengan kemampuan interaksi sosial lansia, kekuatan korelasi sedang dan korelasi bersifat positif. Kesimpulan penelitian adalah terdapat hubungan yang signifikan antara status mental dengan kemampuan interaksi sosial lansia.Kata kunci: status mental; interaksi sosial; lanjut usia